2018
DOI: 10.1152/ajprenal.00266.2018
|View full text |Cite
|
Sign up to set email alerts
|

Soluble (pro)renin receptor as a potential therapy for diabetes insipidus

Abstract: The antidiuretic hormone vasopressin (VP) is produced by the hypothalamus, and is stored and secreted from the posterior pituitary. VP acts via VP type 2 receptors (V2Rs) on the basolateral membrane of principal cells of the collecting duct (CD) to regulate fluid permeability. The VP-evoked endocrine pathway is essential in determining urine concentrating capability. For example, a defect in any component of the VP signaling pathway can result in polyuria, polydipsia, and hypotonic urine, collectively termed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“… 32 , 55 Recent studies have identified a more specific role of sPRR in renal dysfunction which is demonstrated by the fact that sPRR activates the aquaporin 2 (AQP-2) channel in the distal nephron via frizzled-8 and β-catenin signaling pathway and increases water reabsorption. 11 , 56 Another study highlighted the role of sPRR in sodium reabsorption where sPRR upregulates epithelial sodium channel (ENaC) in the distal nephron and increases sodium reabsorption. 57 These findings indicate the role of sPRR in sodium and water homeostasis and the development of subsequent renal dysfunction.…”
Section: Role Of Soluble Prr (Sprr) In Renal Dysfunction and Inflammamentioning
confidence: 99%
“… 32 , 55 Recent studies have identified a more specific role of sPRR in renal dysfunction which is demonstrated by the fact that sPRR activates the aquaporin 2 (AQP-2) channel in the distal nephron via frizzled-8 and β-catenin signaling pathway and increases water reabsorption. 11 , 56 Another study highlighted the role of sPRR in sodium reabsorption where sPRR upregulates epithelial sodium channel (ENaC) in the distal nephron and increases sodium reabsorption. 57 These findings indicate the role of sPRR in sodium and water homeostasis and the development of subsequent renal dysfunction.…”
Section: Role Of Soluble Prr (Sprr) In Renal Dysfunction and Inflammamentioning
confidence: 99%